Transdisciplinarity, Composition, Expression: Reflections on a Spherical Way of Thinking - Sá, Adriana (Leonardo (Oxford), 2024)
Bridging art, music, philosophy, and perception science, this article proposes a spherical way of thinking. The term evokes an inclination to sense connections between all things, implying a transdisciplinary approach to the world. The tensions between differing viewpoints can drive us to think beyond any dichotomy, and uncertainty can inspire creativity. By showing how this possibility is reflected in her work, the author hopes to activate new questions and new ways of addressing those questions.